ANXIETY OF SPEAKING ENGLISH IN ENGLISH FOREIGN LANGUAGE (EFL) CLASS - Rumiyati Rumiyati; Seftika Seftika (STKIP PGRI Lubuklinggau, 2018)
This study aims to investigate the classification level of speaking anxiety, the factors of students anxiety in speaking class and the impacts of anxiety in students speaking performance. This study employed case study design. The subjects of the study were the first semester of EFL students in STKIP Muhammadiyah Pringsewu Lampung consisted of 45 students. There were two types of data, i.e. qualitative data and quantitative data. The result of the research showed that EFL students generally were anxious in speaking English. 39 students have high anxiety, the factors of students anxiety includes three aspects such as communication apprehension, test anxiety, and fear of negative evaluation. Consequently, it affects students speaking performance.